2018
DOI: 10.1210/jc.2017-02773
|View full text |Cite
|
Sign up to set email alerts
|

Pro-FHH: A Risk Equation to Facilitate the Diagnosis of Parathyroid-Related Hypercalcemia

Abstract: Pro-FHH effectively predicted whether a patient has PHPT. A prospective trial is necessary to assess its usefulness in a larger population and in patients with elevated PTH concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 33 publications
2
19
1
Order By: Relevance
“…FHH could have a very similar clinical presentation to primary hyperparathyroidism, and, despite proposed scores and algorithms, it remains difficult to have a precise clinical diagnosis. 13 It is therefore recommended in these cases to exclude a diagnosis of FHH before committing to parathyroidectomy, which is inappropriate in FHH. 14 We were able to analyze the data of 86 patients for whom a genetic diagnosis of FHH was excluded and follow-up information was available.…”
Section: Discussionmentioning
confidence: 99%
“…FHH could have a very similar clinical presentation to primary hyperparathyroidism, and, despite proposed scores and algorithms, it remains difficult to have a precise clinical diagnosis. 13 It is therefore recommended in these cases to exclude a diagnosis of FHH before committing to parathyroidectomy, which is inappropriate in FHH. 14 We were able to analyze the data of 86 patients for whom a genetic diagnosis of FHH was excluded and follow-up information was available.…”
Section: Discussionmentioning
confidence: 99%
“…This is higher than previous estimates of 20‐30%, emphasizing the challenges in getting the diagnosis of hypercalcemic patients correct. In recent studies, additional clinical tools have been suggested to assist the correct diagnosis, for example the Pro‐FHH equation that calculates the probability of PHPT using plasma calcium, osteocalcin, PTH and the 24‐CCCR . Hannan et al developed an algorithm to differentiate between FHH3, caused by variants in codon 15 of the AP2S1 gene, and FHH1 and FHH2, by calculating the CMCR index that uses plasma values of calcium and magnesium and the CCCR .…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, additional clinical tools have been suggested to assist the correct diagnosis, for example the Pro-FHH equation that calculates the probability of PHPT using plasma calcium, osteocalcin, PTH and the 24-CCCR. 26 Hannan et al developed an algorithm to differentiate between FHH3, caused by variants in codon 15 of the AP2S1 gene, and FHH1 and FHH2, by calculating the CMCR index that uses plasma values of calcium and magnesium and the CCCR. 27 The goal of these new clinical tools is to reduce the number of genetic tests performed.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbid vitamin D deficiency, as in this case, will increase PTH levels, and reduce urine CE, making interpretation of biochemistry more difficult. A new risk equation for FHH, Pro‐FHH, using calcium, PTH, urine CCCR, and bone remodeling markers, was recently published; however, it has not been validated in pregnancy . Nuclear medicine imaging is contraindicated during pregnancy, and neck US is operator‐dependent, with no known sensitivity and specificity for use during pregnancy .…”
Section: Discussionmentioning
confidence: 99%